Dietary and economic effects of eliminating shortfall in fruit intake on nutrient intakes and diet cost. Issue 1 (December 2016) - Rehm, Colin; Drewnowski, Adam
Abstract Background Children in the United States do not consume the recommended amounts of fruit. The economic and dietary consequences of meeting the shortfall in fruit consumption have not been evaluated. Methods Analyses were based on a nationally representative sample of 4–18 year-old children (n = 2, 647) from the 2009–2010 National Health and Nutrition Examination Survey (NHANES). The shortfall in total fruit consumption for each child was estimated based on the USDA MyPlate recommendations. The potential impact of filling the shortfall in total fruit consumption was projected with whole fruit alone (WF model) or a combination of 100 % fruit juice and whole fruit (FJ + WF model). Juice consumption was capped using American Academy of Pediatrics (AAP) standards. The USDA national food prices database was used to estimate the cost of meeting the dietary recommendations for fruit. Selected nutrient and mineral intakes, as well as daily diet cost were estimated after eliminating the shortfall in fruit consumption. Results Among all children, vitamin C (+22.8 mg [95 % CI 21.4, 24.1] in the WF model and +48.1 mg [95 % CI 45.2, 51.1] in the FJ + WF model) and potassium intakes (+203 mg [95 % CI 190, 215] in WF and +263 mg [95 % CI 248, 280] in FJ + WF) were increased in both models. The FJ + WF model resulted in a marginal increase in dietary fiber (e.g., a relative change less than 10 %), while the WF model resulted in a meaningful increase in dietary fiber (e.g., a relative change greater than 10 %; +2.2 g [95 % CI 2.1, 2.3]). Conversely, the WF model resulted in only a marginal increase in calcium, while the FJ + WF model resulted in a meaningful increase in calcium (+85 mg [95 % CI 79, 89]). Calories were increased in all models (+4.5 % [95 % CI 4.1, 4.9 %] for FJ + WF and +3.5 % [95 % CI 3.2, 3.7 %] for WF). Meeting the fruit shortfall with whole fruit alone increased estimated diet costs by 9.9 % (+0.44/d [95 % CI 0.42, 0.47]), while the fruit juice/whole fruit combination increased diet costs by 5.2 % (+0.23/d [95 % CI 0.22, 0.25]). Conclusions Meeting fruit consumption guidelines without a substantial increase in diet costs may be a challenge. Combining whole fruit with 100 % fruit juice capped at AAP standards may be one approach to meeting fruit recommendations within cost constraints. Identifying approaches to increasing whole fruit consumption in as cost-neutral a fashion as possible should be a priority.